Finite element analysis of the effects of thermo-mechanical loadings on a tool steel microstructure. (March 2019) - Seriacopi, V.; Fukumasu, N.K.; Souza, R.M.; Machado, I.F.
Abstract: Steels with good toughness and wear resistance, such as the AISI H13, are selected as materials for hot working tools, providing considerable resistance to hot hardness and to thermal fatigue. Moreover, these damages are related to the high stresses and accumulated plastic strain due to the tool-workpiece contact. Based on this context, the proposal of this work is to conduct, by Finite Element Method, thermo-mechanical analysis of tool steel microstructure during the hot forging. This approach considers the differences in terms of mechanical behavior of the phases, which were meshed by OOF2®. ABAQUS® 2016 was also used to simulate loadings applied to the tool throughout one-hundred cycles of hot mechanical processing, initially considering a two-dimensional approach (2D analysis). This simulation provided an evaluation of the influence of the microstructural features on the stress and strain distributions at different temperatures. The main objective consisted in investigating the regions more susceptible to crack nucleation. The results showed that precipitates and interfaces are critical regions for stress concentration. It was also possible to observe a strong evidence of accumulated damage based on an analysis of the excess of dissipated plastic strain energy (EDPSE) over the cycles. EDPSE was four orders of magnitude higher in the thermo-mechanical than in the purely thermal loading conditions. Finally, to support the 2D analyses, a preliminary three-dimensional (3D) numerical model with damage model was developed. The results of the 3D numerical simulations, analyzed in terms of plastic strain fields, showed critical regions where cracks may propagate. These strain distributions and the energy dissipated through damage allow arguing about the change of phase properties to improve microstructural characteristics and tool life. Highlights: Cyclic thermo-mechanical loadings can be result in the hot forging tool damage due to the thermal fatigue. Finite Element Method is an important tool to analyze the critical regions of a microstructure in terms of crack nucleation. The highest stresses have occurred at the precipitates and interfaces. Mechanical loadings provide more accumulated damage than purely thermal loadings. The fracture toughness of the second phase plays an important role in the evaluation of the matrix damage, which accumulates plastic deformation.